Personality and smoking: Individual-participant meta-analysis of 9 cohort studies - Christian Hakulinen; Mirka Hintsanen; Marcus R. Munafò; Marianna Virtanen; Mika Kivimäki; G. David Batty; Markus Jokela (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Aims: To investigate cross-sectional and longitudinal associations between personality and smoking, and test whether sociodemographic factors modify these associations.Design: Cross-sectional and longitudinal individual-participant meta-analysis. Setting: Nine cohort studies from Australia, Germany, UK and US. Participants: A total of 79,757 men and women (mean age = 51 years). Measurements: Personality traits of the Five-Factor Model (extraversion, neuroticism, agreeableness, conscientiousness and openness to experience) were used as exposures. Outcomes were current smoking status (current smoker, ex-smoker, and never smoker), smoking initiation, smoking relapse, and smoking cessation. Associations between personality and smoking were modeled using logistic and multinomial logistic regression, and study-specific findings were combined using random-effect meta-analysis. Findings: Current smoking was associated with higher extraversion (odds ratio per 1 standard deviation increase in the score: 1.16; 95% confidence interval: 1.08-1.24), higher neuroticism (1.19; 1.13-1.26), and lower conscientiousness (0.88; 0.83-0.94). Among nonsmokers, smoking initiation during the follow-up period was prospectively predicted by higher extraversion (1.22; 1.04-1.43) and lower conscientiousness (0.80; 0.68-0.93), whereas higher neuroticism (1.16; 1.04-1.30) predicted smoking relapse among ex-smokers. Among smokers, smoking cessation was negatively associated with neuroticism (0.91; 0.87-0.96). Sociodemographic variables did not appear to modify the associations between personality and smoking. Conclusions: Adult smokers have higher extraversion, higher neuroticism and lower conscientiousness personality scores than non-smokers. Initiation into smoking is positively associated with higher extraversion and lower conscientiousness, while relapse to smoking among ex-smokers is association with higher neuroticism.
Keywords: 330; cohort studies; five-factor mode; individual-participant meta-analysis; personality; smoking